2022
DOI: 10.1029/2022gh000695
|View full text |Cite
|
Sign up to set email alerts
|

Residential and Race/Ethnicity Disparities in Heat Vulnerability in the United States

Abstract: Adverse health outcomes caused by extreme heat represent the most direct human health threat associated with the warming of the Earth's climate. Socioeconomic, demographic, health, land cover, and temperature determinants contribute to heat vulnerability; however, nationwide patterns of residential and race/ethnicity disparities in heat vulnerability in the United States are poorly understood. This study aimed to develop a Heat Vulnerability Index (HVI) for the United States; to assess differences in heat vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Satellites, such as those from the NASA and USGS landsat program, provide 30-meter spatial resolution enabling analysis of heat inequities with more continuity than possible with ground monitors. Of the 22 articles in this review with a focus on heat, 18 articles use LST or other indices to assess urban heat, heat risk or vulnerability [18, 55-61, 64-69, 71-74] and four articles use modeled air temperature derived from satellite measurements of surface temperature [62,63,70,75].…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Satellites, such as those from the NASA and USGS landsat program, provide 30-meter spatial resolution enabling analysis of heat inequities with more continuity than possible with ground monitors. Of the 22 articles in this review with a focus on heat, 18 articles use LST or other indices to assess urban heat, heat risk or vulnerability [18, 55-61, 64-69, 71-74] and four articles use modeled air temperature derived from satellite measurements of surface temperature [62,63,70,75].…”
Section: Temperaturementioning
confidence: 99%
“…The 19 articles had various findings on exposures for minority racial/ethnic groups in different geographies. In thirteen studies, Black, Hispanic and Asian populations had greater exposures to heat in the majority of investigated areas [18,55,58,61,65,66,68,69,72,73,75]. One national study showed that statistically significant racial heat disparities persisted when adjusting for income and when restricting the analysis to smaller rural areas, which are often excluded from heat studies [72].…”
Section: Heat Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Place-based climate health inequities are largely the result of decades of discriminatory policies such as redlining: the intentional concentration of resources and opportunities in predominantly White neighborhoods at the expense of those who identify as Black, Indigenous, and other racial and ethnic minority groups. 11,12 Place-based solutions that deliver community benefits year-round can begin to ameliorate historical deprivation and build social capital and climate resilience. 13,14 Successful initiatives are characterized by a bottom-up approach, whereby outside donors, community development investors, federal/state/local government, and other partners support the communities themselves to identify local problems and priorities and design, manage, and implement solutions.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Such regulation is essential, as ongoing combustion of fossil fuel, coupled with hotter days (leading to more ground level O 3 ) and increasingly common and severe wildfires, pose a serious threat to the universal right to health 202122. Furthermore, areas of socioeconomic disadvantage and those with a high prevalence of minority and other vulnerable groups are already disproportionately affected by poor air quality,20 and faster warming in these areas can exacerbate the inequity further through mechanisms such as increased localized O 3 production 232425. Yet, regulatory standards still rely on geographic averages, rarely accounting for this unequal burden of exposure, let alone synergistic effects.…”
mentioning
confidence: 99%